2014
DOI: 10.3389/fmicb.2014.00699
|View full text |Cite
|
Sign up to set email alerts
|

Oregano essential oil-pectin edible films as anti-quorum sensing and food antimicrobial agents

Abstract: Edible films can be used as carriers for antimicrobial compounds to assure food safety and quality; in addition, pathogenesis of food bacteria is related to a cell to cell communication mechanism called quorum sensing (QS). Oregano essential oil (OEO) has proved to be useful as food antimicrobial; however, its food applications can be compromised by the volatile character of its active constituents. Therefore, formulation of edible films containing OEO can be an alternative to improve its food usages. QS inhib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
54
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 95 publications
(67 citation statements)
references
References 36 publications
12
54
0
1
Order By: Relevance
“…These results show that PMME affect the QS system in C. violaceum ATCC 12472 and C. violaceum CV026, since these strains have reduced violacein production. Similar results for violacein inhibition have been observed with fruit extracts (Oliveira, Rodrigues, Bertoldi, Taylor, & Pinto, ; Rodrigues, Oliveira et al., ; Rodrigues, Zola et al., ; Truchado et al., ; Vattem et al., ), medicinal plants (Rekha, Vasavi, Vipin, Saptami, & Arun, ; Vandeputte et al., ), and spices (Alvarez et al., ; Choo, Rukayadi, & Hwang, ).…”
Section: Resultssupporting
confidence: 67%
See 1 more Smart Citation
“…These results show that PMME affect the QS system in C. violaceum ATCC 12472 and C. violaceum CV026, since these strains have reduced violacein production. Similar results for violacein inhibition have been observed with fruit extracts (Oliveira, Rodrigues, Bertoldi, Taylor, & Pinto, ; Rodrigues, Oliveira et al., ; Rodrigues, Zola et al., ; Truchado et al., ; Vattem et al., ), medicinal plants (Rekha, Vasavi, Vipin, Saptami, & Arun, ; Vandeputte et al., ), and spices (Alvarez et al., ; Choo, Rukayadi, & Hwang, ).…”
Section: Resultssupporting
confidence: 67%
“…Plants are sources of secondary metabolites with potential to interfere in bacterial cell–cell communication (Quecán, Rivera, & Pinto, ). Many studies have evaluated the potential of plant‐rich phenolic extracts to inhibit QS (Alvarez et al., ; Corral‐Lugo, Daddaoua, Ortega, Espinosa‐Urgel, & Krell, ; Jakobsen et al., ; Rasmussen et al., ; Truchado et al., ; Vattem, Mihalik, Crixell, & McLean, ; 2016a; Rodrigues, Oliveira et al., ; Rodrigues, Zola et al., ). Despite the numerous works investigating QS interference, no detailed study on the effect of Capsicum peppers and their major compounds on QS has been reported.…”
Section: Introductionmentioning
confidence: 99%
“…In the plate diffusion assay, the inhibition in this bacterium can be seen as a lack of purple pigmentation around the well, with no detectable alteration on the bacterial growth, as previously observed (Adonizio et al, 2008;Alvarez et al, 2014). However, this assay can only be considered as a preliminary result, since growth inhibition effects exemplified by the colorless transparent halo formed with kanamycin ( Figure 1b) are difficult to be discerned from quorum sensing inhibition which form a turbid colorless halo (Figure 1c and 1c).…”
Section: Discussionmentioning
confidence: 65%
“…Keeping this into consideration, the inhibition of cell-to-cell communication underlying the QS could be considered a viable strategy to ensure food safety and quality (Alvarez et al, 2014;Zhang et al, 2014).…”
Section: Introductionmentioning
confidence: 99%